KEPEMIMPINAN KEPALA SEKOLAH DAN KUALIFIKASI AKADEMIK GURU TERHADAP KINERJA GURU (Studi Kasus di SDIT Ulul Albab Purworejo) - Lailla Hidayatul Amin (MAMBA'UL 'ULUM, 2019)
This study aims to reveal the influence of teachers' perceptions of school leadership and academic qualifications of teachers on teacher performance SDIT Ulul Albab 1 and 2 Purworejo. The approach used in this study is the quantitative approach. The research sample is determined by the formula nomogram Herry King. A population of 58 people with 95% confidence interval, are used to determine 56 people. Based on the results of the descriptive statistical analysis of the variables of school leadership gained a mean of 3.1379, academic qualifications obtained by mean of 2.4483 and teacher performance obtained by mean of 3.8276. There is a positive and significant impact of school leadership on teacher performance of 5.5%. There are no significant negative influence and academic qualifications of teachers on teacher performance of (-) 2.1%. There is the influence of positive and significant impact of school leadership and teachers' academic qualifications together on teacher performance by 0.4%.